An Analysis of scientific research in the field of international financial reporting standards: A Scientometric study - Seyed Mostafa Hassanzadeh Diva; Ghasem Blue; Mohammad Marfou (Iranian Journal of Accounting, Auditing & Finance)
The significance of International Financial Reporting Standards (IFRS) and the interest of a diverse array of global researchers underscore the globalization of financial activities. Despite the substantial volume of publications in this area, the intellectual framework of researchers remains largely unexplored. This research aims to clarify the current state and evolution of this field, highlight the intellectual structure of researchers, and provide new insights for future researchers. The research approach employs scientometrics and data mining. All studies indexed in the Scopus database were analyzed. Word co-occurrence, co-authorship analysis, and Latent Dirichlet Allocation were utilized to create a knowledge map. The co-authorship network analysis by country revealed that the United States, England, Australia, Germany, Italy, Canada, Spain, France, and China exhibited the highest centrality ratings. This research also explored trends and knowledge frontiers over different periods within this scientific domain, which can be categorized into themes such as the acceptance and implementation of IFRS, standard-setting and regulatory frameworks, the quality and transparency of financial reporting, the implications of international standards, corporate governance, and IFRS. The findings provide researchers with a clearer understanding of the existing literature by examining the current state of research in this field. This insight enables them to implement innovative strategies to advance and further develop the scientific discipline. Additionally, researchers can identify potential areas for future studies and interventions by gaining a deeper understanding of the concepts and methodologies within this field.